PEDAGOGICAL DIAGNOSTICS OF DEVELOPING SPIRITUAL WORLDVIEW IN STUDENTS (Scientific journal of the Fergana State University, 2025)
This scientific work is devoted to the study of the issue of pedagogical diagnosis of the development of a spiritual worldview in students. Spiritual worldview is an important factor that determines a person's moral values, beliefs and relationships in social life. The study examines the essence of the concept of spiritual worldview, its role in the educational process, and pedagogical factors influencing the spiritual development of students.